Calibrating a sedimentary record of overwash from Southeastern New England using modeled historic hurricane surges - Boldt, Katherine V.; Lane, Philip; Woodruff, Jonathan D.; Donnelly, Jeffrey P. (Marine Geology, 2010)
We present a 2000-year record of overwash deposits preserved in a backbarrier salt marsh from southeastern New England. The timing of recent deposits matches well with large hurricane-induced storm surge events documented by local tide gauges in 1991, 1960, 1954, and 1938. Storm surge modeling is used to evaluate the flooding history at the site as well as to assess the pre-instrumental historical record. Storms in 1815, 1727, and 1635 likely caused significant surge that overtopped the barrier, with the timing of coarse-grained overwash deposition correlating well with these events. We infer that twenty-three prehistoric layers mapped across the site were likely also deposited by landfalling hurricanes. Additional records from the area will help to evaluate whether or not temporal trends at the site are a robust representation of hurricane activity for the region. The frequency of overwash at Mattapoisett Marsh, on average 1.5 events per century, is significantly higher than many other overwash-based reconstructions from the western North Atlantic. Further, the Mattapoisett Marsh record does not contain significant multi-centennial gaps in overwash layers. This initial comparison of the data from Mattapoisett marsh with other reconstructions from the western North Atlantic may point toward relatively constant tropical cyclone frequency over the last 2000 years with significant variation in the number of intense tropical cyclones.
Keywords: Holocene; hurricane; Paleotempestology; Salt marsh; storm surge; tropical cyclone